Monitoring the psychological state of hockey players in the pre-competitive period - Kondratovich, S. V.; Novakovskiy, S. V.; Kachalov, D. V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to substantiate the effectiveness of the use of express methods for monitoring the individual state of athletes in order to improve performance through timely correction of conditions.